Neuroendocrine Differentiation in Breast Cancer: Clinicopathological Significance of Bcl-2 Positive Solid Papillary Carcinoma - Yoichiro Okubo; Takuji Okubo; Yoshimi Okubo; Takao Ishiwatari (Case Reports in Medicine)
Solid papillary carcinoma (SPC) is considered a rare malignant breast tumor. Maluf and Koerner first reported this disease entity as a special type of ductal carcinoma in situ with several characteristic histopathological features, including low-grade cellular atypia, intracellular or extracellular mucin deposition, and solid papillary growth pattern, as well as neuroendocrine differentiation. The present paper describes a case of SPC with bcl-2 expression, which is known as a marker for malignancy of neuroendocrine tumors. Interestingly, despite bcl-2 expression being a poor prognostic indicator of neuroendocrine tumors, the patient with this tumor has achieved long-term survival (approximately 6 years) at the time of writing this report. Because previous investigators reported that bcl-2 expression might play a role in the inhibition of the development of breast cancer, we suggest that bcl-2 expression might reflect a good prognosis in patients with SPC, rather than being a poor prognostic indicator, as it is in several types of neuroendocrine tumor. However, to confirm this hypothesis, further investigation is required.